Angiopoietin-like protein 3 inhibitors and their effects on hyperlipidemia and atherosclerotic risk - Plengpanich, Wanee (Chulalongkorn Medical Journal, 2024)
Angiopoietin-like protein 3 (ANGPTL3) has emerged as an important regulator of lipid metabolism. Current innovative therapeutic options using monoclonal antibodies, antisense oligonucleotide or vaccine approaches to block this protein may reduce the atherosclerosis risk in individuals with dyslipidemia. This review aimed to discuss the effectiveness of these new ANGPTL3 inhibitors. Currently, evinacumab and vupanorsen are effective ANGPTL3 inhibitors. These drugs are used to treat patients with hyperlipidemia. Moreover, both drugs were associated with a significant reduction in triglyceride and low density lipoprotein levels and may prevent the development of atherosclerosis.